The importance of forgiveness in improving the psychological well-being of victims of infidelity in dating relationships - Aulia, Balqis Isna; Febrieta, Ditta (JURNAL SPIRITS, 2024)
Infidelity is a social phenomenon that is quite familiar in society and causes various problems. One of the negative impacts of infidelity is that the victim experiences low psychological well-being. The method used in this study is a quantitative method with a correlational research type that aims to determine whether there is a positive relationship between forgiveness and psychological well-being. This study involved 130 early adults who had been victims of infidelity in a dating relationship. This study found that Forgiveness contributed 11.08% in improving psychological well-being in victims of infidelity. It was also found that women were more forgiving than men when they were cheated on. In addition, the length of a person's dating period does not affect the forgiveness of victims of infidelity.